2020
DOI: 10.1177/0361198120923359
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Fundamental Diagram Approach to Evaluating the Performance of Regional Traffic Controls

Abstract: Evaluating a regional traffic control system requires understanding both the advantages and disadvantages of control schemes as well as the interrelated characteristics of the system. To assess the efficiency of regional signal control schemes in a road network, this study, which is based on the macroscopic fundamental diagram (MFD) concept, proposes four evaluative indicators: maximum throughput, critical accumulation, gridlock accumulation and the degree of homogeneity. The maximum throughput and gridlock ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The travel-time data for low flow conditions (early morning hours) were filtered, and the 15th percentile travel time of the data was computed and denoted as free-flow travel time ( 33 ). A generalized polynomial function was fitted to the flow–density scatter to estimate the capacity ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
“…The travel-time data for low flow conditions (early morning hours) were filtered, and the 15th percentile travel time of the data was computed and denoted as free-flow travel time ( 33 ). A generalized polynomial function was fitted to the flow–density scatter to estimate the capacity ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
“…Teir feld experiments revealed that there was MFD within a large-scale urban area [4,5]. In several studies, the existing conditions of MFD and its corresponding infuence factors including road infrastructure, trafc demand, signal control strategy, fow distribution, and the driving behaviours were investigated [6][7][8][9]. It was found that a homogeneous network will maintain a well-defned MFD [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Utilizing empirical data from Yokohama, Japan, Geroliminis and Daganzo [22] revealed that MFD is a reproducible and well-defined relationship between space-mean flow, average density, and average speed on an urban network. Since then, MFD has gained widespread popularity and considerable attention due to its outstanding ability in network controlling [23][24][25][26][27][28][29], traffic assignment [30][31][32][33][34], and evaluating network performance [35][36][37]. This paper will also adopt MFD to evaluate the corridor capacity.…”
Section: Mixed Corridor Capacity Evaluation Based On Mfdmentioning
confidence: 99%